2003
DOI: 10.1162/089892903321107792
|View full text |Cite
|
Sign up to set email alerts
|

Visual Localization Ability Influences Cross-Modal Bias

Abstract: The ability of a visual signal to influence the localization of an auditory target (i.e., "cross-modal bias") was examined as a function of the spatial disparity between the two stimuli and their absolute locations in space. Three experimental issues were examined: (a) the effect of a spatially disparate visual stimulus on auditory localization judgments; (b) how the ability to localize visual, auditory, and spatially aligned multisensory (visual-auditory) targets is related to cross-modal bias, and (c) the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
128
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(160 citation statements)
references
References 21 publications
30
128
2
Order By: Relevance
“…The second key aspect of this task which must be included in any full generative model of this problem is that oddity can be entailed in the probe stimulus not only by its combined difference from the standard, but by discrepancy within the probe stimulus. In this case (similar to other recent multisensory perception experiments with variable causal structure : Hairston et al, 2003;Shams et al, 2000Shams et al, , 2005Wallace et al, 2004), the variable structure can effectively "give away" the probe. We introduced the approach needed to solve this type of problem in multisensory perception as structure inference (Hospedales & Vijayakumar, 2008).…”
Section: Modeling Oddity Detectionsupporting
confidence: 76%
See 2 more Smart Citations
“…The second key aspect of this task which must be included in any full generative model of this problem is that oddity can be entailed in the probe stimulus not only by its combined difference from the standard, but by discrepancy within the probe stimulus. In this case (similar to other recent multisensory perception experiments with variable causal structure : Hairston et al, 2003;Shams et al, 2000Shams et al, , 2005Wallace et al, 2004), the variable structure can effectively "give away" the probe. We introduced the approach needed to solve this type of problem in multisensory perception as structure inference (Hospedales & Vijayakumar, 2008).…”
Section: Modeling Oddity Detectionsupporting
confidence: 76%
“…That is, it was not obvious which of multiple possible sources caused the observations (Hairston et al, 2003;Shams, Kamitani, & Shimojo, 2000;Shams, Ma, & Beierholm, 2005;Wallace et al, 2004), or which of multiple possible world models was true (Knill, 2007). In these cases, the standard MLI linear-cue-combination approach fails to explain human performance.…”
Section: Multisensory Oddity Detection As Bayesian Inferencementioning
confidence: 99%
See 1 more Smart Citation
“…From the literature, it appears that they are quite different. For spatial ventriloquism, several behavioral and physiological studies have shown that the spatial ventriloquist effect disappears when the audiovisual temporal alignment is outside a −100 -+ 300 ms window (−100 ms = sound before vision; +300 ms=sound after vision), while the horizontal spatial alignment should not exceed~15° (Godfroy et al, 2003;Hairston, Wallace, Vaughan, Stein, Norris & Schirillo, 2003;Lewald & Guski, 2003;Slutsky & Recanzone, 2001;Radeau & Bertelson, 1977), although the specific degree of tolerated disparities could take a wide range (Wallace, Roberson, Hairston, Stein, Vaughan & Schirillo, 2004).…”
Section: Spatial and Temporal Criteria For Intersensory Pairingmentioning
confidence: 99%
“…These experiments have established 'spatial ventriloquism' [11] in which the perceived location of the auditory component of an auditory/visual multisensory stimulus is displaced in a statistically optimal way towards the component with the least variability in localization estimates [1,9]. The dominance of vision in ventriloquism is compatible with vision usually being the least variable sense in specifying spatial location [22,33].…”
mentioning
confidence: 99%